Building a Diverse Cybersecurity Workforce: A Study on Attracting Learners with Varied Educational Backgrounds - Mubashrah Saddiqa; Kristian Helmer Kjær Larsen1 Helmer Kjær Larsen; Robert Nedergaard Nielsen; Jens Myrup Pedersen (Journal of Cybersecurity Education, Research & Practice, 2023)
Cybersecurity has traditionally been perceived as a highly technical field, centered around hacking, programming, and network defense. However, this article contends that the scope of cybersecurity must transcend its technical confines to embrace a more inclusive approach. By incorporating various concepts such as privacy, data sharing, and ethics, cybersecurity can foster diversity among audiences with varying educational backgrounds, thereby cultivating a richer and more resilient security landscape. A more diverse cybersecurity workforce can provide a broader range of perspectives, experiences, and skills to address the complex and ever-evolving threats of the digital age. The research focuses on enhancing cybersecurity education to attract a diverse audience through the development and testing of a virtual platform on Haaukins (a cybersecurity training platform) designed with features resembling social media for capture-the-flag exercises. The results show that the cyber training platform effectively engages a diverse group of learners, bridging the gap between traditional technical boundaries and the urgent demand for comprehensive cybersecurity competence.